CONTACT OF THE BALOCHI LANGUAGE IN ANCIENT TIMES: AN OVERVIEW - Baloch, Hamid Ali; Sabir, Prof. Dr. Abdul Razzaq (Hanken, 2017)
Balochi has been contact with the Iranian as well as the Indo Aryan Languages from thousands years. In this paper the lexical, morphological, phonological and syntactical changes in Balochi with the contact languages will be synthesized that how Balochi has borrowed or adopted or assimilated the lexemes of the neighboring languages and how the Balochi language played a role as a donor language.